Pelvic malakoplakia presenting as endometrial cancer: a case report - Jeong Soo Cho; Hye In Kim; Jung Yun Lee; Eun Ji Nam; Sunghoon Kim; Young Tae Kim; Sang Wun Kim (Korean Society of Obstetrics and Gynecology, 2020)
Malakoplakia is a rare granulomatous, inflammatory disease generally manifesting as ulcers of the urogenital tract, especially in the bladder, but it can occur in any part of the body. Because of its varied clinical presentations, malakoplakia is considered for differential diagnosis upon suspicion. The final diagnosis is confirmed by the presence of Michaelis-Gutmann bodies. We report a case of pelvic malakoplakia accompanied by left lower quadrant pain that was misdiagnosed as endometrial cancer with pelvic mass based on imaging studies. The patient underwent dilatation and curettage, and the pathology report revealed no malignancy. Because of persistent pain and septic shock, she underwent a debulking operation to remove the mass. Histopathologic examination revealed malakoplakia. For postoperative management, she received broad-spectrum antibiotics, but abdominal pelvic computerized tomography performed on postoperative day 9 revealed pelvic mass recurrence. To the best of our knowledge, this is the only rare case report of pelvic malakoplakia mimicking endometrial cancer.